تأثير التبريد على أداء الأنظمة الفوتوفولتية - كنجو, لانا (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير تبريد اللواقط الشمسية الفوتوفولتية على أدائها، وقد تم ذلك باستخدام برنامج المحاكاة (TRNSYS). حيث تمت نمذجة نظامين فوتوفولتيين ضمن هذا البرنامج أحدهما يمثّل نظاماً تقليدياً غير مبرّد (نظام (PV والآخر نظاماً مبرّداً يمثّله نظام مدمج فوتوفولتي - حراري (PV/T)، وأُجريت المقارنة بينهما من حيث الأداء الذي يعبّر عنه المردود الكهربائي والقدرة الكهربائية لتلك الأنظمة. أمكن الاستفادة من تبريد اللواقط الفوتوفولتية في النظام المدمج في هدف آخر وهو استثمار الحرارة المسحوبة من تلك اللواقط في تسخين الماء لاستخدامه في تطبيقات متعددة. أظهرت نتائج المحاكاة، المنجزة في هذا البحث لمدة عام كامل بخطوة زمنية قدرها ساعة واحدة للنظامين التقليدي (PV) و المدمج (PV/T)، أن المقادير الكهربائية (القدرة والمردود) الوسطية اليومية السنوية للنظام المبرّد بالمقارنة مع النظام غير المبرّد قد ازدادت بحوالي Wh/day (1542 – 370) للقدرة الكهربائية من أجل مساحة متغيرة للاقط الفوتوفولتي m2 (5 – 2)، وكانت الزيادة في المردود الكهربائي من حوالي (3 %) عند مساحة قدرها (2 m2) إلى(6 %) عند مساحة قدرها (5 m2)، كما بلغت كمية الطاقة الحرارية الوسطية اليومية السنوية المسحوبة من اللاقط المبرّد حوالي (3535 – 10445) Wh/day من أجل مساحة متغيرة للاقط الفوتوفولتي من m2 (5 – 1) والتي اُستخدمت لتسخين الماء المار عبر دارة التبريد للنظام المدمج. This research aims to study the influence of cooling the panels of photovoltaic systems on their performance, where this has been done by using simulation program (TRNSYS). Two photovoltaic systems have been modeled within this program. One of them was a traditional system with no-cooling (PV system). The other one was a system with cooling represented by a combined system (thermal – photovoltaic system PV/T). Then, a comparison between them has been done in terms of performance, which has been expressed by electrical power and electrical efficiency. It could exploit the cooling of photovoltaic panels in the combined system. Another objective is to benefit from the heat extracted in water heating for using in many applications. Results of simulations in this research, which have been done for one year by one hour as a step time on the (PV) and (PV/T) systems, showed that the median quotidian annual electrical values for (PV/T) system compared with (PV) system had increased by about (1542 – 370) Wh/day for electrical power at an a variable area of the photovoltaic panel (5 – 2)m2, and the increase in electrical efficiency was from about (3 %) at an area of 2) m2) to about (6 %) at an area 5) m2), also the median quotidian annual thermal energy that had been extracted from the cooling panel reached to (3535 – 10445) Wh/day, at a various area of the electrical panel (5 – 1) m2, which used for heating the water passing through the cooling circuit of the (PV/T) system.